Da História das Ideias Pedagógicas à Mitanálise das Ideias Educativas - Alberto Filipe Araújo (Universidade do Minho, 2001)
In this text, the author analyses the contributions of Nanine Charbonnel and Daniel Hameline for the History of Pedagogical Ideas. Then he presents his own contribution based on three pillars: the Educational Idea, the Idea of Mythical Elements and the Mythanalysis.